Features of the educational process of training coaches and teachers at the university of physical education - Petrov S.I. ,; Terekhina R.N. ,; Medvedeva E.N. ,; Zakrevskaya N.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to theoretical justification of the educational process in the preparation of trainers-teachers in the conditions of integration of educational, scientific and sports activities in universities of physical education. Methods and structure of the study. Based on a synthesis of curriculum monitoring data over 35 years, curricula, educational process schedules and class schedules were analyzed. Results and conclusions. The ratio of educational and sports activities in the process of their integration should take into account the specifics of training in the chosen sport: the age characteristics of the stages of training, the dynamics of the formation of sports skills and the achievement of its peak, the features of the periodization of the training process and planning of the training load. The integration process assumes that the development and implementation of both educational and sports programs takes into account the need for the associated formation of competencies that correspond to the Federal State Educational Standard of Higher Education 49.03.04 Sports and the labor functions of the professional standard «Coach-teacher».